2000
DOI: 10.1007/s002640000116
|View full text |Cite
|
Sign up to set email alerts
|

The midvastus surgical approach in total knee arthroplasty

Abstract: We report a study of 2 surgical approaches to the knee in 42 consecutive patients undergoing a total arthroplasty. They were divided into 2 groups. In Group 1 (n=17) the knee was exposed through classic medial parapatellar arthrotomy and in Group 2 (n=25) the knee was approached through the fibers of the medial vastus. Preoperative assessment did not reveal any statistical differences between the groups, and blood loss, operation time, biochemistry values and radiographic evaluation were also similar. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 22 publications
2
21
0
4
Order By: Relevance
“…The changes in patellar tracking with time with the MPP approach are an important concern for many orthopaedic surgeons [15,20,22,26]. As a result, they use the MV approach instead of the MPP approach in conventional TKAs [8,9,17,31]. The extensor mechanism suffers less damage and the patella is not everted in a MIS TKA, which would result in good patellar tracking and lower incidence of anterior knee pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in patellar tracking with time with the MPP approach are an important concern for many orthopaedic surgeons [15,20,22,26]. As a result, they use the MV approach instead of the MPP approach in conventional TKAs [8,9,17,31]. The extensor mechanism suffers less damage and the patella is not everted in a MIS TKA, which would result in good patellar tracking and lower incidence of anterior knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…last decade, has some potential advantages regarding patellar tracking and lateral retinacular release rate [8,9,17,31]. Therefore, some orthopaedic surgeons use the MV approach rather than the MPP approach to reduce patellar maltracking.…”
mentioning
confidence: 99%
“…17 Parentis et al 18 noted electromyographic abnormalities in vastus medialis in patients undergoing the midvastus approach in 43% of cases compared with none in the medial parapatellar group. Keating et al 19 in a randomized prospective trial reported no differences in range of motion, straight leg raise, and requirement for lateral releases in a series of 100 patients.…”
Section: Midvastus Approachmentioning
confidence: 98%
“…Less blood loss 18 and fewer intraoperative lateral releases have been reported. [17][18][19] There have been equivocal opinions regarding the use of midvastus approach in patients with difficult access. 19,20 Advocates of this approach believe that it is easier to evert the patella with the midvastus approach than with the subvastus approach because of the reduced bulk of the vastus medialis.…”
Section: Midvastus Approachmentioning
confidence: 99%
“…Besides that, full-length coronal radiography did not show more outliers in midvastus group compared with control. Better patellar tracking is expected in midvastus approach, reflected by low rate of lateral retinacular release needed (6)(7)(8)(9). This might be explained by the vastus medialis connections left intact together with quadriceps tendon, resulting in better patellar excursion.…”
Section: The Study Entitled "Comparison Of Mini-midvastus and Conventmentioning
confidence: 99%